Experimental and Numerical Investigation of Self Compacting Reinforced Concrete Dapped End Beams Strengthened with CFRP Sheets (Journal of University of Babylon for Engineering Sciences, 2018)
This study aims to investigate experimentally the behavior of self-compacting reinforced concrete dapped end beams strengthened with CFRP sheets and, then theoretically by ANSYS 15.0 software. The experimental program consists of testing 14-specimens each of dimensions (200x400x1500 mm) with two values of Shear span to depth effective (a/d), namely (1.5 and 1.0). Two of the beams are a control beams (with full reinforcement), and four beams with reduced reinforcement in hanger and nib regions. The other beams have been strengthened with several configurations by CFRP sheets for the same values of (a/d), the comparison between results included load-deflection curves and cracked specimens. It was found that the strut and tie model (STM) is very conservative somehow, reduction the nib reinforcements by about (60%), in reduction in failure load by about (35% and 15%) for the two values of (a/d). With respect to the strengthened specimens, it observed that the strengthening with inclined CFRP strips (450) yielded better results in comparison with other configurations. The improvement in load capacity was about (23%) for (a/d=1.5 and 1.0). Also, it is found that the nonlinear model adopted in the present work compered the experimental tests yielded a good agreement with difference of about (12%).